ISLAM MODERAT DAN RADIKALISME: KAJIAN TEORITIS TENTANG AYAT-AYAT RADIKALISME DALAM PRESPEKTIF ISLAM MODERAT - Huril In; Intia Jul Alfania; Nur Iffah Qoyyumillah; Latifatul Fitriyah; Muhammad Arif Syihabuddin (MAHABBAH : Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2025)
This paper discusses the issue of radicalism in the context of Islam and how views on verses in the Qur'an are often misunderstood to justify acts of violence. With a qualitative approach and descriptive analysis, this study aims to explore verses that are often used as legitimacy by radical groups, as well as provide a contextual understanding from a moderate Islamic perspective. The results of the study show that moderate Islam emphasizes the values of tolerance, peace, and dialogue, which are contrary to radicalism. This research also proposes the importance of education and deradicalization as a method to overcome radicalization and promote a better understanding of islam.